1982
DOI: 10.1177/000348948209100622
|View full text |Cite
|
Sign up to set email alerts
|

Foregut Cysts in Infants and Children

Abstract: The charts of 15 patients with foregut cysts were reviewed. The lesions were intrathoracic in 14 patients and in the cervical area in one child. The importance of early diagnosis and surgical management is stressed. In untreated infants with foregut cysts, severe progressive and life-threatening airway obstruction may develop. Since the symptoms of this congenital lesion may simulate other more common diseases of the tracheobronchial tree and esophagus, the physician should become familiar with this disease en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…Takeda et al [11] found dyspnea and dysphagia as the most common presenting symptoms. Stridor in an infant caused by an esophageal duplication cyst is a rare presentation [14,15]. As was the case with our patient, esophageal duplication cysts rarely connect with the native esophagus, and only two reports were found with connection to the native esophageal lumen [2].…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Takeda et al [11] found dyspnea and dysphagia as the most common presenting symptoms. Stridor in an infant caused by an esophageal duplication cyst is a rare presentation [14,15]. As was the case with our patient, esophageal duplication cysts rarely connect with the native esophagus, and only two reports were found with connection to the native esophageal lumen [2].…”
Section: Discussionsupporting
confidence: 69%
“…Because of the proximity of the lesion to the posterior tracheal wall, and the pliability of the soft tracheal cartilage, the mass provided enough compression to cause significant obstruction with subsequent respiratory difficulty and biphasic stridor. Our case further highlights the fact that esophageal cyst do not communicate with, or attached to the vertebral column [15], which differentiates esophageal from neuroenteric cyst.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…But when a cyst is large, symptoms reflective of respiratory or digestive tract compression may arise including dyspnea, respiratory distress, cough, or dysphagia [4,19]. However, when symptoms develop in early infancy, they are most likely to progress rapidly and produce airway obstruction [20] in the first instance. Although the cystic lesion in our case was completely intramural and located in the cervical esophagus, stridor was the presenting symptom.…”
Section: Discussionmentioning
confidence: 99%